PARTICIPANTS OF MATERIAL PROCESSES IN GRAMMATICAL METAPHORS INVOLVING THE VERBS MAKE AND TAKE - Dede Ismail (Universitas Kuningan, 2020)
This article, based on the transitivity system in a systemic functional linguistic study, is focused on the participants of material processes in grammatical metaphors involving the verbs Make and Take. The objective of this study is to analyze how the participants play a significant role in determining the processes of grammatical metaphors in the clauses. The data were taken from the Corpus of Contemporary American English from 2015 to 2017. The qualitative method was employed since the data were in the form of words rather than numbers. The result of this research showed that the participants of material processes are actors and scopes rather than actors and goals as they commonly occur in material processes. Scopes are represented in the clause since the processes of doing are expressed only by the participants. However, in the congruent forms, the participants of material processes are actors and goals since their participants are expressed as things rather than expressing the process of doing as they occur in the non-congruent forms termed as grammatical metaphors. Keywords: grammatical metaphor; congruent; non-congruent; material processes; participant; goal; scope.